Transformation of Character Education Based on Social Media: Analysis of the Influence of Islamic Educational Videos on Emotional Quotient - Vira Rana Farda (Journal of Indonesian Digital Pedagogy, 2026)
Character education in the digital age finds its extension through social media. Students actively use the Instagram platform as an informal learning tool. This study analyzes the role of the @Pecandu.Sholawat account as a digital pedagogical agent in distributing the value of gratitude and its impact on the emotional intelligence (emotional quotient) of students at Sunan Ampel State Islamic University Surabaya. Using the S-O-R (Stimulus-Organism-Response) theoretical framework, this study positions Islamic video content as an educational stimulus that shapes learners' emotional and spiritual responses. This quantitative study uses simple random sampling and questionnaire-based data collection instruments. A simple linear regression analysis was applied to precisely measure the escalation of emotional intelligence. The regression analysis results proved the significance of the influence of digital educational media, marked by a t-value (6.317) that exceeded the t-table (1.676). The coefficient of determination test yielded a value of 0.454, indicating that Islamic video content accounted for 45.4% of the increase in students’ emotional intelligence. In conclusion, exposure to spiritual content on Instagram serves as an essential digital pedagogical supplement for developing self-awareness, regulating emotions, and internalizing Islamic values among students.